ISOLATION AND IDENTIFICATION OF SHIGELLA SPP. BACTERIA CAUSES OF DIARRHEA IN DOGS - Br Sembiring, Voni Cornelia; Suarjana, I Gusti Ketut; Pasek Gelgel, Ketut Tono (Buletin Veteriner Udayana, 2022)
Dogs are one of the favorite animals that are kept by many people because they are considered intelligent and loyal animals. One of the main health problems of dogs is diarrhea caused by a bacterial infection. Shigella spp. is a pathogenic bacterium in the digestive tract of dogs. This study aims to isolate and identify Shigella spp . bacteria that cause diarrhea in dogs. Samples studied using rectal swabs in dogs showing clinical symptoms of diarrhea with a total of 48 samples from veterinary clinics in the city of Denpasar and its surroundings. Isolation of Shigella spp. was conducted on Eosin Methylene Blue Agar, Salmonella-Shigella Agar, and Sheep Blood Agar. Colonies that grew and separated on Salmonella-Shigella Agar medium were subjected to Gram staining, catalase test, oxidase test and continued with biochemical tests, namely Triple Sugar Iron Agar, Sulfid Indole Motility, Methyl Red Voges Proskauer, Simmons Citrate Agar, and test for sugars such as glucose, lactose, mannitol, and arabinose. The results showed that of the 48 isolated and identified samples, one sample showed a positive result for Shigella spp. with possibly the species Shigella dysentriae . It was concluded that one (2.08%) of Shigella spp . bacteria could be isolated and identified from 48 samples of dog rectal swabs that showed clinical symptoms of diarrhea. It is necessary to conduct further research on the level of pathogenicity of Shigella spp. bacteria and for further research, it is necessary to supplement the API 20E test to determine the Shigella species.